Sustainable Entrepreneurship: Innovative Solutions for Achieving SDGs in Indonesia 2030 - Sungkawati, Endang (CV. Bimbingan Belajar Assyfa, 2024)
Amidst the global challenge to achieve the Sustainable Development Goals (SDGs) by 2030, sustainable entrepreneurship offers an innovative solution for Indonesia. This study aims to explore the role of sustainable entrepreneurship in supporting the achievement of SDGs in Indonesia. Using a narrative literature review, this study analyzed 35 scientific articles published between 2019 and 2023. The subjects of the study involved social entrepreneurs and small and medium enterprises in the environmental and social sectors. The instrument used was content analysis focused on entrepreneurial strategies and their impact on SDGs. The results of the study indicate that sustainable entrepreneurship initiatives can increase resource efficiency by up to 40% and accelerate the achievement of at least 5 of the 17 SDGs. In addition, entrepreneurship that emphasizes sustainable practices shows increased competitiveness and cross-sector collaboration. In conclusion, sustainable entrepreneurship is not only an economic tool but also an important driver in achieving SDGs. This study recommends that the government and private sector strengthen support for sustainable entrepreneurship initiatives through appropriate policies and incentives.